2020
DOI: 10.18203/2320-6012.ijrms20202896
|View full text |Cite
|
Sign up to set email alerts
|

Role of biomarkers in predicting anastomotic leakage following colorectal surgeries

Abstract: Background: Recovery after surgery for patients with colorectal disease has improved with the advent of minimal access surgery and standardized recovery protocols. Despite these advances, anastomotic leakage remains one of the most dreaded complications following colorectal surgery, with rates of 3-27 per cent depending on specific risk factors. The aim of the study was to assess sensitivity and specificity of systemic and peritoneal drain-fluid bio-markers in early prediction of anastomotic leak; and to co-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“… Essa et al (2021) [ 10 ]; Almeida et al (2011) [ 11 ]; Ellebæk et al (2014) [ 12 ]; Garcia-Granero et al (2013) [ 13 ]; Giaccaglia et al (2014) [ 14 ]; Giaccaglia et al (2016) [ 15 ]; Käser et al (2014) [ 16 ]; Kørner et al (2009) [ 17 ]; Wani et al (2020) [ 18 ]; Ortega-Deballon et al (2010) [ 19 ]; Platt et al (2012) [ 20 ]; Welsch et al (2007) [ 22 ]. …”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“… Essa et al (2021) [ 10 ]; Almeida et al (2011) [ 11 ]; Ellebæk et al (2014) [ 12 ]; Garcia-Granero et al (2013) [ 13 ]; Giaccaglia et al (2014) [ 14 ]; Giaccaglia et al (2016) [ 15 ]; Käser et al (2014) [ 16 ]; Kørner et al (2009) [ 17 ]; Wani et al (2020) [ 18 ]; Ortega-Deballon et al (2010) [ 19 ]; Platt et al (2012) [ 20 ]; Welsch et al (2007) [ 22 ]. …”
Section: Reviewmentioning
confidence: 99%
“…The study by Wani et al [ 18 ] reported the highest value (0.3636), whereas the study by Giaccaglia et al (2016) reported the lowest value (0.058) [ 15 ]. The size of the square varied according to the sample size of the study.…”
Section: Reviewmentioning
confidence: 99%